Unveiling the Critical Link: Periodontal Disease and Overall Health (Bangladesh Journal of Medical Science, 2024)
Background:  Periodontal disease, a chronic inflammatory condition affecting the gums and surrounding tissues, has long been recognized as a threat to oral health. However, emerging research increasingly reveals its profound implications for overall health. This editorial delves into the intricate connection between periodontal disease and systemic health, shedding light on the far-reaching consequences of untreated gum disease.Conclusion:  The evidence presented underscores the urgency of addressing periodontal disease not only as an oral health concern but also as a critical component of comprehensive healthcare. By recognizing and addressing the link between periodontal disease and systemic health, healthcare professionals can better prevent and manage a myriad of conditions, ultimately improving patient outcomes and quality of life.Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S7-S8